Analisis UU Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi dalam Perspektif Kepentingan Umum: Studi Banding dengan GDPR Uni Eropa, PDPA Singapore, dan DPA Filipina - Bagus Kurniawan Susanto; Vonda Aprilianto; Salasatri Rafaa Dinni; Faiz Nashrillah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) in relation to the public interest, and compares it with regulations in the European Union (GDPR), Singapore (PDPA), and the Philippines (DPA). The findings in this study indicate that although the PDP Law aims to protect people's personal data, in each of its applications it still faces major problems, especially because there is no independent supervisory institution with clear responsibilities and authorities. Unlike the GDPR, PDPA, and DPA which already have strong supervisory mechanisms, the PDP Law still has weaknesses in terms of law enforcement and imposing sanctions on violators. Therefore, this study recommends the establishment of an independent supervisory body with clear authority so that personal data protection in Indonesia is more effective, efficient and can restore public trust in the security of their data.